Two-phase numerical simulation of hybrid nanofluid heat transfer in minichannel heat sink and experimental validation - Kumar V.; Sarkar J. (My University, 2025)
Nanofluid cooled mini-micro channel heat sink has become a pleasant alternative for electronics and thermal applications recently due to its compactness and enhanced heat transfer characteristics. In the present study, a numerical simulation on laminar forced convection flow of DI water based Al2O3 nanofluid and Al2O3-MWCNT hybrid nanofluid in minichannel heat sink has been performed using two-phase mixture model to investigate the heat transfer and pressure drop characteristics. The experimental study on hybrid nanofluid flow in minichannel heat sink has also been conducted and validated the numerical model. Effect of some important parameters, such as, hydraulic diameter, channel aspect ratio, composition of Al2O3 and MWCNT in hybrid nanofluid and Reynold number has been investigated as well. Two-phase (heterogeneous) model has good agreement with the experiment result as compared to single phase (homogenous) approach. Maximum heat transfer coefficient has been found for 0.01 vol% (Al2O3 + MWCNT) (7:3) hybrid nanofluid for minichannel depth of 0.5 mm. Pressure drop has been found maximum for minichannel of 0.5 mm channel depth. The developing length can increase by using nanofluid. Maximum heat transfer coefficient improvement of 15.6% has been observed with no appreciable increment in pressure drop by using hybrid nanofluids. © 2017 Elsevier Ltd